Pengaruh Layanan Mobile Banking Terhadap Jumlah Nasabah Menabung Pada PT. Bank Syariah Indonesia, Tbk Kcp Stabat - Fuja Novani; Kamaliah R; Khairunnisa Khairunnisa (Al-Sharf: Jurnal Ekonomi Islam, 2022)
This research aims to determine the effect of mobile banking services on the number of customers saving at PT. Bank Syariah Indonesia, Tbk. KCP Stabat. The research method used in this study is quantitative using simple linear regression analysis techniques. It was obtained that in the R2 test the coefficient of determination was 0.225 (22.5%). That is, the number of customers saving at PT. Bank Syariah Indonesia, Tbk. KCP Stabat was affected by mobile banking services by 22.5% The remaining 77.5% was influenced by other factors besides mobile banking services. The t test showed that tcount (3,489) > ttable (1.68). That is, mobile banking services have a significant effect on the number of customers saving at PT. Bank Syariah Indonesia, Tbk. KCP Stabat with a p-value of 0.000 < 0.05. The result of the mobile banking service variable regression coefficient is 0.413 which means that if the variable value of mobile banking services increases by 1, it will be followed by an increase in the number of customers saving by 0.394 so that the better mobile banking services performed, the higher the level of public savings.